Zróżnicowanie i zmienność cen detalicznych produktów mleczarskich po akcesji do Unii Europejskiej - Kozłowski, Wojciech (Differentiation and Variability of Retail Prices of Milk Products after the European Union Accession, 2005)
The main goal of this research is to evaluate the level of differentiation and variability of prices of selected milk products in the Olsztyn network of retail stores before and after the Poland's accession to the European Union. The empirical price analyses show the significant increase of prices of milk products and changes in their differentiation after the EU enlargement. In spite of geographical limitation of this research to the local market it is possible to assume that the rules observed in this market are also characteristic of the other spatial markets in Poland. Further and faster equalization of prices of domestic and European milk products can be anticipated in the nearest future and as a consequence the decrease of price advantage of Polish milk industry in the European market can be anticipated as well.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 490-495